Assessment the unused capacity using time driven activity based costing in automotive manufacturing industry - N. F. A., Ghani; S. N. A. M., Zaini; Mohd Yazid, Abu (Penerbit UMP, 2020)
Automotive Manufacturing Industry usually known implementing all six sigma method and lean manufacturing. However, actual practicality in the world of manufacturing, there are a lot of factors contributes that become the challenge to the ideal of lean production line. Not exclude those factors, there is no methods to identify the possible lost cost by the factors. This research is to identify the used and unused capacity exist in production line that considering factors affecting the production line at real time. Time-driven activity-based costing (TDABC) is identified as one of the powerful tools to analyze the actual condition of production. Cost-driver rate is defined in Phase 3 where the highest capacity cost rate calculated is RM0.67 per minutes which involving Station 3, Station 5, Station 7 and Station 8. The least capacity cost rate is RM0.33 per minutes recorded by Station 0(Preparation), Station 2 and Station 6. Ten time equations for each station at trim line is developed. During the development of time equation, criticality of Station 7 when it became the only station affected with all thirteen factors listed can be seen as station that needed focus for improvement or target for lean manufacturing. In regards of the relevancy of applying TimeDriven Activity-Based Costing, as a whole, TD-ABC can be used to identify the estimation capacity used either over or underused. Not only unused capacity is identified, but result shows Station 0 is overused by 2932 minutes equals to RM967.56. Therefore, based on the result obtained, station with overused capacity and several stations with underused capacity gives a clear overview to the management of the company for better investment strategy.